Reference equations for tidal breathing parameters using structured light plethysmography - Motamedi-Fakhr, Shayan; Iles, Richard; Barker, Nicki; Alexander, John; Cooper, Brendan G. (ERJ open research, 2021)
Tidal breathing measurements can be used to identify changes in respiratory status. Structured light plethysmography (SLP) is a non-contact tidal breathing measurement technique. Lack of reference equations for SLP parameters makes clinical decision-making difficult. We have developed a set of growth-adjusted reference equations for seven clinically pertinent parameters of respiratory rate ( f R ), inspiratory time ( t I ), expiratory time ( t E ), duty cycle ( t I /total breath time), phase (thoraco-abdominal asynchrony (TAA)), relative thoracic contribution (RTC) and tidal inspiratory/expiratory flow at 50% volume (IE50). Reference equations were developed based on a cohort of 198 seated healthy subjects (age 2–75 years, height 82–194 cm, 108 males). We adopted the same methodological approach as the Global Lung Function Initiative (GLI) report on spirometric reference equations. 5 min of tidal breathing was recorded per subject. Parameters were summarised with their medians. The supplementary material provided is an integral part of this work and a reference range calculator is provided therein. We found predicted f R to decrease with age and height rapidly in the first 20 years and slowly thereafter. Expected t I , t E and RTC followed the opposite trend. RTC was 6.7% higher in females. Duty cycle increased with age, peaked at 13 years and decreased thereafter. TAA was high and variable in early life and declined rapidly with age. Predicted IE50 was constant, as it did not correlate with growth. These reference ranges for seven key measures ensure that clinicians and researchers can identify tidal breathing patterns in disease and better understand and interpret SLP and tidal breathing data.